Management of the Potential of Silalahi III Tourism Village, Silahisabungan District, Dairi Regency - Tamba, Joel Parluhutan; Kamal, Mustafa; Daulay, Ferdianto Yusuf (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this research is to analyze village management as well as supporting and inhibiting factors in the management of potential Silalahi III tourism villages, Silahisabungan sub district, Dairi district, North Sumatra province. The method used in this research is descriptive qualitative research method. The data collection technique in this research is a data collection method in a way that can be used by researchers to collect data according to Riduan (2010:51). The results of research on the potential management of cultural villages as villages in Dairi Regency show that the 5 management functions according to Hendry Fayol, namely Planning, Organizing, Commanding, Coordinating and Controlling, are the initial and important steps. for the human resource development process in Silalahi III village as a cultural tourism village that has been recognized by the regent, so it is hoped that this tourism village can develop and be sustainable. As a result, the main obstacle is human resources being the main reason. The government needs to develop local culture and wisdom, both tangible and intangible, as a trigger for community economic development, especially in the Silalahi III Culture village.